CDIO Framework: A Solution of The Project-Based Learning Problem in Accounting Study Program - Fadillah, Fadillah -; Zelmiyanti, Riri; Irianto, Danar; Riadi, Sugeng (Pusat P2M Politeknik Negeri Batam, 2024)
This study assesses the readiness of the accounting Study Program at Batam State Polytechnic in implementing CDIO as a PBL-based MBKM support. Although PBL has been integrated in education there, constraints such as inefficient schedules are still common. Qualitative descriptive method is used by conducting interviews with related parties. The results showed that the initial implementation of CDIO involves the division of the project in one semester supported by relevant subjects. By implementing CDIO, it is expected to reduce constraints during PBL, improve time efficiency, and course management involved in the project. It is recommended that accounting study programs continue to prepare themselves in implementing CDIO and involve relevant courses to support PBL